Perbedaan Kadar Gula Darah Setelah Terapi Bekam Basah Dan Pijat Refleksi Pada Penderita Diabetes Mellitus Di Karangmalang Sragen - WULANDARI, RATRI, Winarsih Nur Ambarwati, S. Kep., Ns., ETN., M. Kep, Arief Wahyudi Jadmiko, S. Kep., Ns., M. Kep (2015)
Diabetes mellitus is one of the non-communicable diseases that occur on a person because an increase blood glucose levels as a result of progressive insulin secretion because decreased insulin resistance. Many non-pharmacological therapy have been found to help reduce and control blood glucose levels, such as wet cupping therapy and reflexology. Wet cupping therapy can increase blood circulation in the pancreas and in the muscles so that increased insulin receptor sensitivity and glucose levels is decreased, whereas reflexology is able to provide stimulus that is capable to make blood circulate smoothly through the body. This research aimed to determin of the differences in blood glucose after wet cupping therapy and reflexology. This research method used pre-experimental design with two group pre-post design. Total sample in this study was 60 respondents, divided into 2 groups with 30 persons for wet cupping therapy and 30 persons for reflexology. The sampling method used accidental sampling. Data analysis techniques using paired sample t-test to find out blood sugar before and after theraphy in both groups, whereas difference test between wet cupping therapy and reflexology use independent sample t-test. From the result of test paired sample t-test showed that p-value 0.001 in both groups H0 was rejected, there are differences in blood glucose levels before and after wet cupping therapy and reflexology. From the result of independent sample t-test showed that p-value 0,046 and mean difference in both groups were -21.457, so H0 was rejected, there are differences in blood sugar levels after wet cupping therapy and after reflexology, and wet cupping therapy more effective than reflexology in reducing blood sugar levels.